ANALISIS KEPUASAN MASYARAKAT TERHADAP LAYANAN BISKITA TRANS PAKUAN BOGOR TAHUN 2025 - Razlina Tsania Putri; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
Public transportation plays a crucial role in supporting urban mobility and reducing the use of private vehicles. The presence of Biskita Trans Pakuan Bogor is expected to serve as a solution to mobility issues and traffic congestion in the city. However, operational challenges such as limited routes, insufficient fleet availability, and the temporary suspension of services in early 2025 have made the analysis of public satisfaction increasingly relevant. This study aims to examine the level of public satisfaction with the Biskita Trans Pakuan Bogor service and to identify the factors that influence it. This research employs a mixed-methods approach with a sequential explanatory design, beginning with quantitative data collection through questionnaires distributed to 100 respondents, followed by qualitative interviews with the Head of the Transportation Division at the Bogor City Transportation Agency and five Biskita users. Quantitative data were analyzed using descriptive statistical techniques, while qualitative analysis involved data reduction, data display, and conclusion drawing. The findings indicate that, overall, Biskita Trans Pakuan Bogor has provided a satisfactory level of service to the public. Three indicators, requirements, cost , and product specifications of service received the highest satisfaction levels, as all respondents gave positive assessments without expressing dissatisfaction. Meanwhile, other indicators, including system, mechanism, and procedure, timeliness, staff competence, staff behavior, handling of complaints, suggestions and feedback, as well as facilities and infrastructure, still showed the presence of respondents who felt less satisfied. Nevertheless, the service as a whole meets public expectations and offers safe and comfortable transportation..